DIGITAL GAMES - A MAGICAL LEARNING TOOL FOR SLOW LEARNERS - Albert, Paul (International Journal of Research -GRANTHAALAYAH, 2018)
The present article mainly focused on how digital or computer games act as a fruitful learning tool for slow learners through game based learning. Also, it describes that among many learning methods, game based learning is a suitable way using digital games for slow learners especially for digital natives. In addition, the present article highlighted the educational benefits and effectiveness of digital games. Further, it explores some digital games that can be used in the educational context. Finally the present article suggested that the digital games can be used as a tool in teaching and learning process for slow learners.